What is the best proportion of fish meal and soybean meal for better growth and survival of Macrobrachiurn rosenbergii post Larvae? - Mohamed, Rozihan; B.A., John; C.R, Saad; Khan Chowdhury, Ahmed Jalal (Knowledgia Review, 2012)

(untitled)
The effect of partial and complete substitution of fishmeal (FM) for Soy Bean Meal (SBM) on the growth and survival of Macrobrachium rosenbergii were studied. Post larvae (PL 28) with an average individual length (16.20±0.20 mm) and weight (0.032±0.002 g) were stocked in aquarium filled with 5.0 L of water for a period of eight weeks. Six types of diets with different percentage of FM:SBM ratios were formulated and fed to the test animals at the ratio of 0:100, 20:80, 40:60, 60:40, 80:20, 100:0 (diet 1-6, respectively). Significant differences in terms of body weight and orbital length of animal were observed between diets 2, 3, 4, 5 and diets 1 and 6. Larvae fed with diet 3 produced the highest mean weight gain 0.711 g. There was no significant difference in weight gain observed in experiment provided with diet 2, 4 and 5 (~0.4-0.5 g). Larvae fed with diet 1 and 6 showed less weight gain (~0.2 g) with highest percentage of survival (70%) in diet 6 experimental tank. Food Conversion Ratio (FCR), Protein Efficiency Ratio (PER) and Specific Growth Rate (SGR) were also calculated for each experimental diets besides analyzing their proximate composition. It can be concluded that soy bean (diet 3) could be used for the better growth of M. rosenbergii post larvae. It was also understood that complete removal or absolute utilization of fish meal (100%) in diet would directly affect the weight gain in fresh water prawn (p<0.05). [Fulltext PDF] [Fulltext HTML] [XML: Abstract + Referen